Entrepreneurs' socioeconomic status and government expropriation in an emerging economy - Zhou, Jieyu; Ge, Lipeng Gary; Li, Jiatao; Chandrashekar, Subramanya Prasad (Strategic Entrepreneurship Journal, 2020)
Abstract Research Summary This study focuses on a salient challenge for entrepreneurs in emerging economies: government expropriation. Drawing on signaling arguments, we propose that an owner's high socioeconomic status (SES) attracts government attention to her start‐up by conveying information about its resource endowments. The empirical tests based on start‐ups in China support that an owner's high SES increases government expropriation. The effect is stronger for start‐ups in regions with greater income inequality or in those where the legal system is less developed. High‐SES entrepreneurs can mitigate the risk of government expropriation by building political connections. Managerial Summary Institutional voids in emerging economies pose a major threat to start‐ups in the form of government expropriation. This research finds that the threat is more severe for start‐ups with high‐SES entrepreneurs because they have strong resource‐mobilization capabilities and easily become expropriation targets. Further, this research suggests that two measures help protect high‐SES entrepreneurs from government expropriation: locating their start‐ups in regions with low income inequality or a well‐developed legal system, and building connections with the government in order to exchange favors with government officials.